Which factors influence revenues of a Prague wine bar? - Winklerová, Nina; Stroukal, Dominik, 1987-; Šťastný, Dan, 1974-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
This paper studies the factors which influence the revenues of a Prague wine bar. Among the factors temperature, rainfall, events, Friday or Saturday, and prohibition are considered. I use daily data from multiple sources between January 2010 and December 2012. With the aid of regression analysis, I found out that prohibition of alcohol stronger than 20% did not have an impact on revenues. Also rainfall does not influence the revenues, but temperature does. Revenues increase when temperature goes up to a certain point and then decrease. Both occurrence of events and Friday or Saturday increase the revenues.
Vedoucí práce: Dominik Stroukal
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses